Generation of hemophilia A mouse induced pluripotent stem cells using polycistronic lentiviral vector in serum- and feeder-free culture conditions - M. Sakri, Rozita; Abdullah, Syahril; Mohamed Said, Mohamed Saifulaman (Frontiers Research Foundation, 2016)
Induced pluripotent stem cells (iPSCs) research has opened up exciting possibilities in many research areas especially in the field of regenerative medicine. The ability to reprogram back somatic cells into embryonic stem (ES)-like state has made patient-specific cells therapy possible unhindered ethical and practical dilemmas associated with the use of embryonic stem cells [1]. There have been several reports on the generation of iPS cells from murine somatic cells in vitro, however, there are still many challenges to overcome; (i) the induction efficiency is extremely low, (ii) multiple transgene integrations which increase the risk of tumorigenicity of iPS cells produced, (iii) partially differentiated iPS colonies due to incomplete reprogramming, (iv) the use of feeder cells and medium containing serum add complexity and variability in nutrients and factors that contribute to cell growth and the maintenance of pluripotency [2,3,4,5]. To overcome these issues, we utilized polycistronic lentiviral vector carrying the Yamanaka’s factors (Oct4, Sox2, Klf4 and c-Myc) for reprogramming of murine fibroblasts in serum- and feeder- free defined culture conditions.